Higher education, the health care industry, and metropolitan regional economic development: What can "Eds & Meds" do for the economic fortunes of a metro area's residents? - Timothy J. Bartik; George Erickcek (W.E. Upjohn Institute for Employment Research, 2007)
This paper examines the effects of expansions in higher educational institutions and the medical service industry on the economic development of a metropolitan area. This examination pulls together previous research and provides some new empirical evidence. We provide quantitative evidence of the magnitude of economic effects of higher education and medical service industries that occur through the mechanism of providing some export-base demand stimulus to a metropolitan economy. We also provide quantitative evidence on how much higher education institutions can boost a metropolitan economy through increasing the educational attainment of local residence. We estimate that medical service industries pay above average wages, holding worker characteristics constant, whereas the higher education industry pays below average wages; the wage standards of these industries may affect overall metropolitan wages. We also discuss other mechanisms by which these two industries may boost a metropolitan economy, including: increasing local amenities, generating R&D spillovers, increasing the rate of entrepreneurship in local businesses, and helping provide local leadership on development and growth issues. Finally, the paper discusses possible effects of these two industries on disparities between the central city and suburbs in a metropolitan area.
Keywords: R58; R11; R23; R53; 330